Human Centered Design First International Conference, HCD 2009, Held as Part of HCI International 2009, San Diego, CA, USA, July 19-24, 2009 Proceedings - Kurosu, Masaaki (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2009)
This volume constitutes the refereed proceedings of the First International Conference on Human Centered Design, HCD 2009, held in San Diego, CA, USA in July 2009, as part of the 13th International Conference on Human-Computer Interaction, HCI International 2009 jointly with 9 other thematically similar conferences. The 125 revised papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical parts on usability and user experience, methods and techniques for HCD, understanding diverse human needs and requirements, HCD in industry, HCD for web-based applications and services, HCD at work, as well as user involvement and participatory methods.